2015
DOI: 10.1186/s13102-015-0018-5
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of ten consumer activity trackers

Abstract: BackgroundActivity trackers can potentially stimulate users to increase their physical activity behavior. The aim of this study was to examine the reliability and validity of ten consumer activity trackers for measuring step count in both laboratory and free-living conditions.MethodHealthy adult volunteers (n = 33) walked twice on a treadmill (4.8 km/h) for 30 min while wearing ten different activity trackers (i.e. Lumoback, Fitbit Flex, Jawbone Up, Nike+ Fuelband SE, Misfit Shine, Withings Pulse, Fitbit Zip, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
276
10
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(320 citation statements)
references
References 33 publications
19
276
10
5
Order By: Relevance
“…Therefore, available evidence suggests that step estimations from CPAMs are both more reliable and more valid than kcal estimations. The correlations obtained in the present study were comparable to those reported by Diaz et al for steps (0.97 vs. 0.99) and kcals (0.94 vs. 0.97), as well as those of Takacs et al [11] for steps (0.96 vs. 1.00), respectively [8,10]. It is important to note the consistently high correlations across various activity protocols indicating that reliability remains high even with the inclusion of a variety of activities, contrasting validity research where inclusion of diverse activities lowers CPAM validity [18].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, available evidence suggests that step estimations from CPAMs are both more reliable and more valid than kcal estimations. The correlations obtained in the present study were comparable to those reported by Diaz et al for steps (0.97 vs. 0.99) and kcals (0.94 vs. 0.97), as well as those of Takacs et al [11] for steps (0.96 vs. 1.00), respectively [8,10]. It is important to note the consistently high correlations across various activity protocols indicating that reliability remains high even with the inclusion of a variety of activities, contrasting validity research where inclusion of diverse activities lowers CPAM validity [18].…”
Section: Discussionsupporting
confidence: 92%
“…The ICCs in the present study are higher than those found by Kooiman et al [8] who determined intra-monitor reliability for steps using the FF, JU, and FZ; their ICCs were 0.81, 0.83, and 0.90, respectively compared to 0.89, 0.88, and 0.99 in our study also using a laboratory setting [8]. Discrepancies between the studies could be attributable to differences in activity protocols.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In recent years fashionable gadgets, such as Fitbit, Jawbone UP and Nike+ Fuelband SE, have appeared in the consumer electronics market [14]. Such fitness devices demonstrate the rise of a trend towards self-monitoring, as well as the willingness of users to wear them.…”
Section: Related Workmentioning
confidence: 99%
“…Until now, only activity trackers have been scrutinized for their validity [14][15][16][17][18][19][20]. These studies found that most activity trackers (Fitbit Flex, Fitbit Zip, Fitbit One, Fitbit Charge HR, Jawbone Up, Nike+ Fuelband SE, Misfit Shine, Withings Pulse) are valid for measuring steps, but to a lesser extent for measuring MVPA.…”
Section: Introductionmentioning
confidence: 99%